PELAKSANAAN KONSENSUALISME DAN IKTIKAD BAIK YANG SEIMBANG BAGI PARA PIHAK DALAM PERJANJIAN BANGUN BAGI HASIL PEMBANGUNAN RUKO MENURUT KUHPERDATA - Hardiyanto, Yudi (Menara Ilmu, 2017)
This type of research is observational reseach by means of a survey, the research thattakes data directly from the population / respondents by conducting interviews andquestionnaire as a data collection tool, then the data are taken from the processing performedin order to obtain a conclusion by inductive methods.From the results of research and discussion by the author that the implementation ofconsensual principle and good faith are balanced for both parties in agreement constructingdividingof shophouses development according to the Indonesian civil code in implementationshould be properly addressed if the developer will do agreement well so that the landownerdid not suffer material losses.The implementation agreement constructing-dividing for the development outcomes ofthis shophouses is not run in a balanced manner because the developer build first shophousesof landowners with conditions that do not conform to the agreement and then build his ownshophouses so that landowners suffered material losses.Keyword: agreement constructing-dividing, concensual, good-faith, civil code